Fecal Keratin 8 Is a Noninvasive and Specific Marker for Intestinal Injury in Necrotizing Enterocolitis - Kewei Wang; Guozhong Tao; Zhen Sun; Jingjing Wei; Junlin Liu; Jordan Taylor; Michelle Gibson; Mirko Mostaghimi; Misty Good; Karl G. Sylvester (Journal of Immunology Research, 2023)
Specific biomarkers of intestinal injury associated with necrotizing enterocolitis (NEC) are needed to diagnose and monitor intestinal mucosal injury and recovery. This study aims to develop and test a modified enzyme-linked immunosorbent assay (ELISA) protocol to detect the total keratin 8 (K8) in the stool of newborns with NEC and investigate the clinical value of fecal K8 as a marker of intestinal injury specifically associated with NEC. We collected fecal samples from five newborns with NEC and five gestational age-matched premature neonates without NEC at the Lucile Packard Children’s Hospital Stanford and Washington University School of Medicine, respectively. Fecal K8 levels were measured using a modified ELISA protocol and Western blot, and fecal calprotectin was measured using a commercial ELISA kit. Clinical data, including gestational age, birth weight, Bell stage for NEC, feeding strategies, total white blood cell (WBC) count, and other pertinent clinical variables, were collected and analyzed. Fecal K8 levels were significantly higher in the pre-NEC group (1–2 days before diagnosis of NEC) and NEC group than those in the non-NEC group (p=0.013, p=0.041). Moreover, fecal K8 was relatively higher at the onset of NEC and declined after the resolution of the disease (p=0.019). Results with similar trends to fecal K8 were also seen in fecal calprotectin (p=0.046), but not seen in total WBC count (p=0.182). In conclusion, a modified ELISA protocol for the total K8 protein was successfully developed for the detection of fecal K8 in the clinical setting of premature newborns with NEC. Fecal K8 is noted to be significantly increased in premature newborns with NEC and may, therefore, serve as a noninvasive and specific marker for intestinal epithelial injury associated with NEC.